EVALUATING CUTTING TRANSPORT ON 12 ¼” SECTION WELL TM-1 - Ratna Widyaningsih; Kharisma Idea; Ayu Utami; Ristiyan Ragil Putradianto; Dhika Permana Jati; Pratama Dzulfiansyah; Puji Hartoyo (Journal of Petroleum and Geothermal Technology, 2024)
Mud hydraulics on a 12-1/4" section needs to be planned properly. Mud hydraulics design on a 12-1/4" section includes determining mud density, flow type, pressure loss, pump specifications, bit hydraulics and cutting lifting design. The purpose of bit hydraulics design is to determine the optimum flow rate. Mud hydraulics optimization is carried out using methods the Bit Hydraulic Horse Power (BHHP), Bit Hydraulic Impact (BHI) and Jet Velocity (JV) methods, where the analysis is in the form of graphs. The graph is analyzed by using a trial and error method to obtain the recommended flow rate so as to provide good cutting lifting. where the expected recommendation analysis are Cutting Transport Ratio (Ft) > 90%, Cutting Concentration (Ca) < 5%, and Carrying Capacity Index (CCI) > 1. The analysis results from the graph show that for the hole 12-1/4", it is recommended to use an optimum flow rate of 626.6 gpm with minimum value of Ft is 90.01%, Ca is 0.87% and CCI is 1.95. These values are stated to be good by using 15-15-16 nozzle bit combination. The Flowrate value can be increased up to 785 gpm by using 18-18-20 nozzle bit combination.. Keywords: Hydraulic Mud Planning, Optimum Flow Rate, Cuttings Removal.